Molecular detection of Trypanosoma minasense in captive black-faced black spider monkeys Ateles chamek (mammalia; primate) - Kmetiuk, Louise Bach; Passerino, Ana Silvia Miranda; Bonat, Marcelo; Morikawa, Vívien Midori; Berbigier, Alice Pereira; Roque, André Luiz Rodrigues; Figueiredo, Fabiano Borges; Biondo, Alexander Welker (Frontiers in Veterinary Science, 2025)
The present study aimed to assess Trypanosoma spp. infection in 17 captive black-faced black spider monkeys (Ateles chamek), living at the Zoological Garden of Curitiba, Paraná, Brazil. Blood samples (3 mL) were collected by femoral puncture by certified veterinarians. A total of 5 μL of extracted blood DNA was submitted to Nested-PCR 18S rDNA. In overall, 4/17 (23.5%) spider monkeys were positive to Trypanosoma spp. by PCR. Sequencing results for 18S rDNA revealed Trypanosoma minasense infection. This is the first report of T. minasense in black-faced black spider monkey worldwide and the first assessment of Trypanosoma species in NHP of southern Brazil.